2017
DOI: 10.21037/jtd.2017.07.46
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary metastasectomy in uterine malignancies: outcome and prognostic factors

Abstract: IntroductionUterine malignancies (UM) include different histologies with different behaviors and outcomes. Endometrial adenocarcinoma (EA) is the most frequent type followed by papillary serous adenocarcinoma (PSA) and uterine leiomyosarcoma (UL). According to Surveillance, Epidemiology, and End Results (SEER) (1) the percentage of new cases of endometrial cancer (EC) compared to all cancers every year is 3.6% with a rate of death equal to 1.8%. Squamous cell carcinoma (SCC) represents the most frequent cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Cervical cancer is highly linked to preventable sexually acquired infection with certain types of HPV (16 and 18) [3]. HPV infection has been shown as the primary agent of cervical cancer and it can be diagnosed through routine screening based on clinical history and/or physical findings and confirmed by cervical punch or cone biopsy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is highly linked to preventable sexually acquired infection with certain types of HPV (16 and 18) [3]. HPV infection has been shown as the primary agent of cervical cancer and it can be diagnosed through routine screening based on clinical history and/or physical findings and confirmed by cervical punch or cone biopsy [4].…”
Section: Introductionmentioning
confidence: 99%
“…≥ 3; histology: non-Sq Clavero et al 13 a 2006 1985–2001 70 20 40 7 47 (34–63) (Univariate) DFI < 24 months; primary site: cervix, adjuvant chemotherapy after the initial gynecologic cancer operation Paramanathan and Wright 14 2013 2001–2011 13 0 13 0 66 (NA) NA Adachi et al 15 a 2015 1985–2013 23 4 0 14 82 (NA) (Univariate) DFI < 24 months Paik et al 16 2015 1995–2011 29 21 8 0 48 (NA) (Univariate) symptomatic, tumor no. ≥ 3 Anile et al 17 2017 1997–2010 19 12 4 3 41 (NA) (Multivariate) DFI < 24 months, recurrence after PM Present study 2020 2006–2015 57 25 9 23 69 (54–81) (Univariate) DFI ≤ 24 months Ca carcinoma, CI confidence interval, DFI disease-free interval, NA not available, PM pulmonary metastasectomy, ...…”
Section: Discussionmentioning
confidence: 93%
“…Previous reports on PM for uterine malignancies from 2001 in the English literature are shown in Table 4. [10][11][12][13][14][15][16][17] The numbers of patients ranged from 13 to 133, and the 5-year OS rates ranged from 47 to 82%. In the present study and three previous studies, DFI was shown to have a significant influence on long-term survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient had all of these factors and her prognosis was considered good. Surgical resection is a viable option in cases of pulmonary metastasis, including from uterine cancers, and pulmonary metastasectomy using VATS is a safe and feasible procedure in cases with primary uterine malginancies 11 …”
Section: Discussionmentioning
confidence: 99%